2012
DOI: 10.1002/bit.24780
|View full text |Cite
|
Sign up to set email alerts
|

A simple eccentric stirred tank mini‐bioreactor: Mixing characterization and mammalian cell culture experiments

Abstract: In industrial practice, stirred tank bioreactors are the most common mammalian cell culture platform. However, research and screening protocols at the laboratory scale (i.e., 5-100 mL) rely primarily on Petri dishes, culture bottles, or Erlenmeyer flasks. There is a clear need for simple-easy to assemble, easy to use, easy to clean-cell culture mini-bioreactors for lab-scale and/or screening applications. Here, we study the mixing performance and culture adequacy of a 30 mL eccentric stirred tank mini-bioreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
(99 reference statements)
0
22
0
Order By: Relevance
“…Figure 4 illustrate these findings, showing different mixing conditions or states in a stirred tank containing a blue maize non-Newtonian flour suspension. In Figure 4a , which depicts a tank stirred by an eccentrically located inclined disc impeller [36] , [37] , a subsurface acid injection was efficiently dispersed to achieve a practically (at least visually) homogeneous condition in less than 5 minutes. In Figure 4b , we show the final state of mixing of a similar experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 illustrate these findings, showing different mixing conditions or states in a stirred tank containing a blue maize non-Newtonian flour suspension. In Figure 4a , which depicts a tank stirred by an eccentrically located inclined disc impeller [36] , [37] , a subsurface acid injection was efficiently dispersed to achieve a practically (at least visually) homogeneous condition in less than 5 minutes. In Figure 4b , we show the final state of mixing of a similar experiment.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the stirring configuration studied here would provide adequate mixing in laminar vessels at lower RPM values (and consequently lower tip speed values) than other configurations. This can be very useful in the context of culture of shear‐sensitive cells, such as CHO cells, stem cells, plant cells, and fungus broths (see also Bulnes‐Abundis et al, 2012) . In practice, this also implies adequate mixing at lower power input and shear stress.…”
Section: Resultsmentioning
confidence: 99%
“…Laminar mixing scenarios are not uncommon in industrial practice. Some relevant examples are the agitation of high‐viscosity materials in the food industry and in the manufacture of lubricants, the formulation of cosmetics such as creams and unguents, the mixing of liquid detergents, and the agitation of shear‐sensitive cells (fungi, plant, insect, and animal cells) in the biopharmaceutical/biotechnology industries . In the specific case of biotechnology applications, and particularly in laboratory‐scale experiments (for the screening of cell culture conditions, the selection of high‐producing clones, or the definition of culture medium, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach unveiled a surprisingly rich dynamics of the mixing process even in remarkably simple flows, thus establishing a strong connection between chaotic behavior of fluid element trajectories and mixing efficiency . Based on these concepts, the possibility of obtaining efficient mixing in stirred tanks processing highly viscous fluid was extensively investigated in a series of works, which identified symmetry‐breaking of the equipment geometry as one of the most effective routes to massive chaotic behavior . For instance, in contrast to what a naive, intuition‐based approach would suggest, it was showed that whenever laminar regime prevails, an eccentric placement of the stirrer in a cylindrical vessel could shrink down the mixing time by orders of magnitude when compared to the standard symmetric configuration.…”
Section: Introductionmentioning
confidence: 99%